2002
DOI: 10.1271/bbb.66.754
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Cold-active Alkaline Phosphatase Gene of a Psychrophile,Shewanellasp., and Expression of the Recombinant Enzyme

Abstract: A psychrophilic alkaline phosphatase (EC 3.1.3.1) from Shewanella sp. is a cold-active enzyme that has high catalytic activity at low temperature [Ishida et al. (1998) Biosci. Biotechnol. Biochem., 62, 2246-2250]. Here, we identified the nucleotide sequence of a gene encoding the enzyme after cloning with the polymerase chain reaction (PCR) and inverted PCR techniques. The deduced amino acid sequence of the enzyme contained conserved amino acids found among mesophilic alkaline phosphatases and showed some stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…The species of Shewanella identified in our study had different activity, but as there are many different species within the genus, multiple phosphatases are likely. At present, the type(s) of phosphatase(s) in the three species identified in this study are not known, although several studies Murakawa et al 2002;Yasuda et al 2002;Yamaguchi et al 2006;Tsuruta et al 2010) have examined phosphatase production in Shewanella spp. The species of bacteria identified in our study probably produce a phosphatase that degrades AMP to AdR in shrimp.…”
Section: Bacterial Degradation Of Ampmentioning
confidence: 89%
“…The species of Shewanella identified in our study had different activity, but as there are many different species within the genus, multiple phosphatases are likely. At present, the type(s) of phosphatase(s) in the three species identified in this study are not known, although several studies Murakawa et al 2002;Yasuda et al 2002;Yamaguchi et al 2006;Tsuruta et al 2010) have examined phosphatase production in Shewanella spp. The species of bacteria identified in our study probably produce a phosphatase that degrades AMP to AdR in shrimp.…”
Section: Bacterial Degradation Of Ampmentioning
confidence: 89%
“…[17][18][19] Previously, we reported that RNase HI 22) and FKBP22 23) from Shewanella sp. SIB1 show the highest amino acid sequence identities, of 78% and 85% respectively, to those from Shewanella oneidensis MR-1.…”
Section: Cloningmentioning
confidence: 99%
“…30) It shows amino acid sequence identities of 62% to SCAPase, 19) 33% to TAB5 APase, 17) 37% to E. coli APase, 31) 42% to B. subtilis APase III, 32) 35% to Thermus sp. FD3041 APase (unpublished, accession no.…”
Section: Amino Acid Sequencementioning
confidence: 99%
See 2 more Smart Citations